Recuperação da modulação autonômica cardíaca após sessão de exercícios com a haste oscilatória - António, Ana Márcia dos Santos [UNESP] (2014)
This study aimed to analyze the effects of exercise with flexible pole in the recovery of cardiac autonomic modulation in healthy women. In this context, the first part of this report is to analyze the effects of an exercise protocol with flexible pole in the recovery of cardiac autonomic modulation by means of heart rate variability in healthy women, since it lacks in the literature evidence from studies with similar characteristics. To complement the dissertation, the second part of the study aimed to describe the response of cardiac autonomic recovery in isometric exercise, which is well known for generating great physiological stress on the cardiovascular system, however, the heart rate response in this exercise has been used to study the modulation of the autonomic nervous system on the heart. The observational study was conducted in 32 healthy women who performed an exercise protocol with the flexible pole and analyzed the pre-exercise heart rate variability: 10 minutes before exercise, 0-5 minutes, 5-10 minutes, 10- 15 minutes after exercise...